2010
DOI: 10.4314/afrrev.v4i2.58286
|View full text |Cite
|
Sign up to set email alerts
|

Accident Prediction Models for Akure – Ondo Carriageway, Ondo State Southwest Nigeria; Using Multiple Linear Regressions

Abstract: Accident data on the 52km Akure-Ondo Carriageway and Spot Speed data were collected and analyzed. The analysis of the Spot Speed gives an average of 51.5km/hr and 110.75km/hr for the 15 th and 85 th percentile speed respectively, the 85 th percentile speed is higher than the posted speed limit of 60km/hr which indicate that the vehicle travelling at this speed are susceptible to accident. The analysis for the study area also shows that 759 peopled were involved in the accidents, 108 persons were killed and abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The drive time of 60 km/hr was used because it represents the average maximum drive speed on highways. Owoaje et al (2005) and Oyedepo and Makinde (2010) noted that a vehicle traveling above this speed limit is susceptible to accident. The number of LGAs that are within 2, 4, 6, 8 and 10 hr drive times from the existing NCDCMLs were evaluated as baseline scenarios.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drive time of 60 km/hr was used because it represents the average maximum drive speed on highways. Owoaje et al (2005) and Oyedepo and Makinde (2010) noted that a vehicle traveling above this speed limit is susceptible to accident. The number of LGAs that are within 2, 4, 6, 8 and 10 hr drive times from the existing NCDCMLs were evaluated as baseline scenarios.…”
Section: Methodsmentioning
confidence: 99%
“…The 60 km/hr benchmark was used because of the poor quality of most roads, especially intracity roads as well as those roads connecting rural communities to large urban centers (Nwachukwu, 2014). Furthermore, it represents the average maximum drive speed on highways and vehicle traveling above this speed limit is susceptible to accident (Owoaje et al, 2005;Oyedepo & Makinde, 2010).These factors may have limited the number of LGAs within the drive times considered. It should also be noted that the use of actual roadnetwork as opposed to Euclidean distance might also have reduced the number of LGAs within the 60 km/hr drive time.…”
Section: Additional Three Utrhs Facility With 2 4 6 8 and 10 Hr Drivetimementioning
confidence: 99%
“…7 Accident prediction models were developed for Akure-Ondo carriageway using multiple linear regression. 8 The spot speed analysis indicated that higher value of 85th percentile contributed to the accidents on the carriageway with a posted speed limit of 60 km/hr; other contributing factors stated are drivers' behaviour, poorly maintained vehicles, non-adherence to traffic rules, poorly maintained road and verges, and over-speeding.…”
Section: Literature Reviewmentioning
confidence: 99%